‘Our bones are made of Iron’: the political ecology of Garhwali women's activism - Drew, Georgina (The Australian journal of anthropology, 2014)
In the Garhwal Himalaya of India's Uttarakhand State, a series of social movements emerged in the late 2000s to contest hydroelectric dams on a tributary of the sacred River Ganga. Within these opposition movements, men often took high-profile leadership roles whereas women from a range of socio-economic backgrounds formed the overwhelming base of participation at meetings, assemblies, and rallies. This article draws from event-based participation and semi-structured interviews to explore the diverse concerns that women gave to explain their engagements with opposition efforts. I counter essentialist frames and employ a feminist political ecology approach to argue that the gendered dynamics are attributable to historical, cultural, religious, and political-economic influences. The article contributes to anthropologies of gender, environment, and social movements by taking an approach focused on disparities of practice and power that helps situate Garhwali women's roles in development contestations.